Macroeconomic Uncertainty and Risk: Collective Optimism of Small-Business Owners. (September 2022) - Patel, Pankaj C.; Tsionas, Mike
How small-business owners assess uncertainty and risk in the macroeconomic environment to report optimism toward their business activity is an important research question for policymakers and academics alike. Drawing on a monthly optimism index and a variety of uncertainty and volatility (risk) trackers from January 1986 to June 2017, in line with the expectation that business owners dislike uncertainty in economic policy, economic policy uncertainty may lower optimism. Business investment and sentiment volatility, however, contributed positively to optimism. The findings provide preliminary implications for policymakers in targeting indicators salient to the optimism index of small-business owners.